A Review: Microbial Diversity and Function of Fermented Meat Products in China - Wang, Zhengli; Wang, Zhengxi; Ji, Lili; Zhang, Jiamin; Zhao, Zhiping; Zhang, Rui; Bai, Ting; Hou, Bo; Zhang, Yin; Liu, Dayu; Wang, Wei; Chen, Lin (Frontiers in Microbiology, 2021)
Fermented meat products have a long history in China. These products exhibit a characteristic unique flavor, compact meat quality, clear color, long shelf life and wide variety and are easy to transport. During the processing and storage of fermented meat products, microorganisms are present and exhibit diverse characteristics. Microorganisms can accelerate the degradation of proteins and fats to produce flavor compounds, inhibit the growth and reproduction of heterozygous bacteria, and reduce the content of chemical pollutants. This paper reviews the microbial diversity of Chinese ham, sausage, preserved meat, pressed salted duck, preserved fish and air-dried meat and provides analyses of the microbial compositions of various products. Due to the differences in raw materials, technology, auxiliary materials and fermentation technology, the microbial species found in various fermented meat products in China are different. However, most fermented meat products in China are subjected to pickling and fermentation, so their microbial compositions also have similarities. Microorganisms in fermented meat products mainly include staphylococci, lactobacilli, micrococci, yeasts and molds. The study of microbial diversity is of great significance for the formation of quality flavor and the safety control of fermented meat products, and it provides some theoretical reference for the study of fermented meat products in China.